Pendidikan Gerejawi dan Pengharapan Eskatologis: Menata Ulang Pembentukan Iman Kristen untuk Keselamatan di Era Modern - Nadeak, Uli Erni; Ruben Nesimnasi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
In the context of modernity, characterized by secularization and existential anxiety, traditional models of Christian faith formation often appear disconnected from the lived reality of believers, particularly regarding the doctrines of salvation and eschatology. This study investigates the crucial role of the church in bridging this gap by developing a pedagogical approach that integrally links ecclesial education with eschatological hope. Employing a qualitative descriptive analysis method, this research examines theological literature, contemporary church documents, and case studies of Christian formation programs. The analysis reveals that a robust eschatological perspective oriented towards the hope of salvation, resurrection, and the renewal of all things is not merely a final chapter of doctrine but an essential, transformative framework for all faith education. It shapes Christian identity, ethics, and mission in the present. The study concludes that for faith formation to be salvific and relevant today, the church must intentionally reconfigure its educational praxis. This reconfiguration involves moving from a compartmentalized teaching of